Chemical Speciation and Mobility of Heavy Metals in Soils Around Nasara Sack and Packaging Company Akwanga, Nigeria (JOURNAL OF ADVANCES IN CHEMISTRY, 2019)
This study quantified and assessed the mobility of iron, nickel, cobalt and lead in soils around a sack and packaging company using indices such as mobility factor and risk assessment code. The results evaluating the mobility factor of heavy metals in soils around the sack and packaging company reveal that all the metals determined exceed the minimum limit of 10% mobility factor and are mobile with the mobility factor being in the order of: Ni > Pb > Co > Fe in the test soil. The risk assessment of heavy metals in the area based on risk assessment code ranged from low risk to medium risk (1-30%) where the risk level of the heavy metals is in the order:  Co > Ni > Pb > Fe in the test soil.